2008
DOI: 10.1080/13504850600993614
|View full text |Cite
|
Sign up to set email alerts
|

Episodic dependencies in Central and Eastern Europe stock markets

Abstract: This article introduces a modified version of the Hinich and Patterson (1995) windowed-test procedure and uses it to detect linear and nonlinear dependencies in the case of six Central and East European stock markets. Testing the original methodology leads us to the same conclusions as those found on other emerging markets: relatively long random walk periods are interrupted by short and intense linear and/or nonlinear correlations. But, our findings diverge when we run the modified test procedure, additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…The settlement of this hypothesis is based on the general characteristic of emergent markets according to which disclosed information is more slowly reflected by the stock price, and investors have longer reaction time (Todea and Zoicaş-Ienciu 2008). We correlate our hypothesis to the findings of the study conducted by Barth and Clinch (1999) who consider that revaluations which date back to more than 3 years are more relevant for the Australian market.…”
Section: Hypothesis 4 (H4) Several Year-old Revalued Amounts Have Supmentioning
confidence: 90%
See 1 more Smart Citation
“…The settlement of this hypothesis is based on the general characteristic of emergent markets according to which disclosed information is more slowly reflected by the stock price, and investors have longer reaction time (Todea and Zoicaş-Ienciu 2008). We correlate our hypothesis to the findings of the study conducted by Barth and Clinch (1999) who consider that revaluations which date back to more than 3 years are more relevant for the Australian market.…”
Section: Hypothesis 4 (H4) Several Year-old Revalued Amounts Have Supmentioning
confidence: 90%
“…Market capitalization went from 2,999 million euro in 2003 to 24,601 million euro in 2007 (BVB 2009). Recent studies on the Romanian market show a low degree of semi-strong efficiency (Todea and Zoicaş-Ienciu 2008;Zoicas-Ienciu 2008). However, a significant effect of disclosed financial earnings on the share price was determined through an event study.…”
Section: The Sample and The Analysis Modelmentioning
confidence: 98%
“…Another group of studies applies existing weak‐form EMH tests in rolling estimation windows 14 . Examples are the rolling VR tests (Tabak, 2003; Kim and Shamsuddin, 2008; Hung, 2009), rolling ADF unit root test (Phengpis, 2006), rolling bicorrelation test (Lim, 2007; Todea and Zoicas‐Ienciu, 2008), rolling parameters of ARCH models (Degiannakis et al , 2008; Alagidede and Panagiotidis, 2009a) and rolling Hurst exponent (Costa and Vasconcelos, 2003; Cajueiro and Tabak, 2004b, 2005d, 2006, 2008; Zunino et al , 2007). The application of a rolling window essentially captures the persistence of stock price departures from a random walk benchmark over time.…”
Section: Rolling Estimation Windows With Fixed Parameter In Each Wmentioning
confidence: 99%
“…Such behaviour could contribute to effects of SAD variable as observed in this research. Moreover, Todea and Zoicas-Ienciu (2008) by using window-test procedure of Hinich and Patterson found that Hungarian, Czech, Slovakian, Polish, and Romanian markets exhibited windows of rejecting the random walk hypothesis. Since episodes of such behaviour exist on those markets, it is not unusual to expect that investors' preferences change on such markets.…”
Section: Empirical Analysismentioning
confidence: 99%